Urban mobility in modern China: the growth of the e-bike - Zuev, D. (2018)
This book is an empirically rich case-study of what is currently the most popular alternative-fuel vehicle in the history of motorization – the electric two-wheeler (e-bike). The book provides sociological insights into e-bike mobility in China and discusses politics, social practices and larger issues of mobility transition in urban China. Taking an accessible approach to the subject, the book identifies the main sociospatial conflicts regarding the use of e-bikes and discusses why electric two-wheeler mobility is important for the future of urban China and urban transportation globally. This book will be an invaluable read for urban geographers and transportation researchers, but also for academics and general readers interested in Chinese Studies, specifically in the area of urban mobility in China.